Preparation method and application of lithium tantalate single crystal film
By growing lithium tantalate single crystals on lithium niobate wafers and using their corrosion rate differences for chemical corrosion, the problems in the prior art that are difficult to take into account low cost, high crystal quality and controllable thickness are solved, and the preparation and application of large-size high-quality lithium tantalate single crystal thin films are realized.
Patent Information
- Application Number
- CN202411977356.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-05-02
AI Technical Summary
The existing technology is difficult to take into account the problems of low cost, high crystal quality and controllable thickness, which makes it difficult to apply lithium tantalate single crystal thin films on a large scale in practical applications.
Grow lithium tantalate single crystals on lithium niobate wafers, and one side of them is bonded to the slide. Through thinning and chemical corrosion steps, the corrosion rate difference between lithium niobate single crystals and lithium tantalate single crystals is gradually removed to obtain a nano-scale large-size high-quality lithium tantalate single crystals bonded to the slide.
The preparation of large-size high-quality lithium tantalate single crystal thin film with controllable thickness is realized, which reduces process costs, increases yield rate, and breaks down the application barriers of lithium tantalate single crystal thin film.
Smart Images

Figure CN119913618A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing a lithium tantalate single crystal thin film and its application, belonging to the field of semiconductor technology. Background Art
[0002] Lithium tantalate single crystal has high Curie temperature (~660℃), high pyroelectric coefficient (~2.0×10 -8 C cm -2 ·K -1 ), excellent electro-optical conversion performance, strong resistance to photorefractive index, good piezoelectric properties, etc., make it show broad application prospects in infrared sensing, optical communication, optical computing, electronic communication and other fields. The reduction of lithium tantalate single crystal thickness plays a key role in improving heat dissipation efficiency, reducing packaging volume, reducing internal stress and improving device performance. With the development of integration and miniaturization in the fields of optical communication and optical computing, in order to realize the integration of multiple devices and improve the integration and performance of the system, requirements are put forward for the preparation of large-size, high-quality lithium tantalate single crystal films.
[0003] At present, there are three main methods for preparing lithium tantalate single crystal thin films: (1) Mechanical thinning. This method can quickly remove the material on the surface of the wafer through physical friction by mechanical grinding, which has the advantages of high efficiency and low cost. However, the thinning process can easily cause surface damage and internal stress on the wafer, and subsequent processes are usually required to improve the surface quality. The thickness of the lithium tantalate single crystal prepared by mechanical thinning is usually 20-100μm, and it is difficult to prepare a lithium tantalate single crystal thin film with high precision and uniformity. (2) Smart-Cut technology. This technology combines ion implantation stripping and wafer bonding to transfer thin layers of material from one wafer to another while maintaining high crystal quality and flatness. Smart-Cut technology uses ion implantation stripping and wafer bonding to prepare highly uniform and high-quality thin films with a film thickness of less than 1μm. However, this method has problems such as low bonding yield, high preparation cost, and high environmental purity requirements. (3) Direct growth. Common preparation methods for lithium tantalate thin films include sol-gel method and magnetron sputtering method. The advantage of the sol-gel method is its high cost-effectiveness, but its disadvantage is that the quality of the film cannot be controlled. However, since single crystal silicon is usually used as the substrate, the lithium tantalate film prepared is mostly polycrystalline lithium tantalate film, and its performance is inferior to that of single crystal lithium tantalate film.
[0004] In summary, although mechanical thinning has the advantages of high efficiency and low cost, it is difficult to prepare nano-scale lithium tantalate single crystal films; wafer-level nano-scale lithium tantalate single crystal films can be achieved using Smart-Cut technology, but it has problems such as low bonding yield and high cost, which limits the large-scale application of lithium tantalate single crystal films in practice; although the direct preparation method can obtain lithium tantalate films with controllable thickness, most of the lithium tantalate films prepared are polycrystalline lithium tantalate films, and their performance is not as good as that of lithium tantalate single crystal films. Therefore, how to prepare high-quality and large-size lithium tantalate single crystal films efficiently and at low cost is an urgent problem to be solved. Summary of the invention
[0005] In order to solve the problem that it is difficult to achieve low cost, high crystal quality and controllable thickness in the existing technology for preparing lithium tantalate single crystal thin films, the present application proposes a processing technology solution that can achieve large-area lithium tantalate single crystal thin films with controllable thickness. The technology solution first grows lithium tantalate single crystals on lithium niobate wafers, bonds one side of the lithium tantalate to a carrier, and then thins the lithium niobate single crystal to less than 50μm by thinning. Then, the difference in corrosion rate between lithium niobate single crystals and lithium tantalate single crystals is used to etch away the upper lithium niobate single crystals with acid solutions such as hydrofluoric acid and aqua regia, and finally a nanoscale large-size, high-quality lithium tantalate single crystal film bonded to the carrier is obtained. This method has the advantages of low cost, high crystal quality and controllable thickness, and can achieve the preparation of nanoscale lithium tantalate single crystal thin films.
[0006] This application adopts the following technical solutions:
[0007] According to the first aspect of the present application, a method for preparing a lithium tantalate single crystal thin film is provided, comprising the following steps:
[0008] Provide carrier wafers and lithium niobate single crystal substrates;
[0009] epitaxially growing a lithium tantalate single crystal layer on the lithium niobate single crystal substrate;
[0010] Bonding one side of the lithium tantalate single crystal layer of the lithium niobate single crystal substrate to the carrier through a curing adhesive to obtain a bonding sheet;
[0011] Thinning the lithium niobate single crystal substrate in the bonding sheet to form a lithium niobate single crystal film;
[0012] The lithium niobate single crystal film is chemically etched until the lithium tantalate single crystal layer is exposed, thereby obtaining the lithium tantalate single crystal film bonded to the carrier.
[0013] In one embodiment, the thickness of the lithium tantalate single crystal layer is less than or equal to 20 μm.
[0014] In one embodiment, the thickness of the lithium niobate single crystal film is less than or equal to 50 μm.
[0015] In one embodiment, the chemical etching step includes immersing the bonding wafer after forming the lithium niobate single crystal thin film in an etching solution;
[0016] The etching solution is selected from at least one of hydrofluoric acid, concentrated sulfuric acid, aqua regia, and BOE solution.
[0017] In one embodiment, after the chemical etching is performed to expose the lithium tantalate single crystal layer, the process further includes performing surface treatment on the lithium tantalate single crystal layer.
[0018] In one embodiment, the steps further include:
[0019] The lithium tantalate single crystal film bonded to the carrier is debonded to obtain the separated lithium tantalate single crystal film.
[0020] In one embodiment, the carrier is selected from one of glass, silicon wafer, and flexible polymer film.
[0021] In one embodiment, the size of the lithium tantalate single crystal film is 4 to 12 inches.
[0022] According to the first aspect of the present application, there is provided an application of the above-mentioned method for preparing lithium tantalate single crystal thin film in the preparation of electronic devices and optical devices.
[0023] In one embodiment, the method for preparing a lithium tantalate single crystal thin film further includes the following steps:
[0024] After epitaxially growing a lithium tantalate single crystal layer on the lithium niobate single crystal substrate, a device array is prepared on the lithium tantalate single crystal layer by a semiconductor process;
[0025] After obtaining the lithium tantalate single crystal film bonded to the carrier, the side of the lithium tantalate single crystal film facing away from the carrier is bonded to a target substrate, and then the carrier and the lithium tantalate single crystal film are separated by debonding.
[0026] The beneficial effects of this application include:
[0027] (1) The method for preparing lithium tantalate single crystal thin films provided in the present application can realize the preparation of large-size (4-12 inches) high-quality lithium tantalate single crystal thin films with controllable thickness.
[0028] (2) The method for preparing a lithium tantalate single crystal thin film provided in the present application can bond the prepared lithium tantalate single crystal thin film to any desired carrier, thus breaking through the application barrier of the lithium tantalate single crystal thin film.
[0029] (3) The method for preparing lithium tantalate single crystal thin films provided in the present application can realize high-quality batch preparation of lithium tantalate single crystal thin films, greatly reducing process costs and improving the yield rate of lithium tantalate single crystal thin films. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a flow chart of the method for preparing lithium tantalate single crystal thin film of the present application.
[0031] Figure 2 This is a structural cross-sectional view of a lithium tantalate single crystal thin film after preparation in the lithium tantalate single crystal thin film preparation method of the present application;
[0032] Figure 3 This is a cross-sectional view of the structure after bonding in the method for preparing a lithium tantalate single crystal thin film of the present application;
[0033] Figure 4 This is a cross-sectional view of the structure after thinning in the method for preparing a lithium tantalate single crystal thin film of the present application;
[0034] Figure 5 This is a structural cross-sectional view of lithium niobate after chemical etching in the lithium tantalate single crystal thin film preparation method of the present application. DETAILED DESCRIPTION
[0035] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0036] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0037] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.
[0038] The main methods for preparing lithium tantalate single crystal thin films are currently mechanical thinning, Smart-Cut, and direct preparation methods, but all of them have certain defects or shortcomings: Although mechanical thinning has the advantages of high efficiency and low cost, it is difficult to prepare lithium tantalate single crystal thin films with nanometer-level thickness. The Smart-Cut technology can be used to prepare large-scale nanoscale lithium tantalate single crystal thin films, but its low bonding yield greatly increases the preparation cost of single crystal thin films, which limits the large-scale application of lithium tantalate single crystal thin films in practice. Although the direct preparation method can obtain lithium tantalate thin films with controllable thickness, most of the lithium tantalate thin films prepared are polycrystalline lithium tantalate thin films, and their performance is not as good as that of lithium tantalate single crystal thin films. Therefore, how to prepare high-quality and large-size lithium tantalate single crystal thin films efficiently and at low cost is a problem that needs to be solved urgently.
[0039] In order to solve at least one of the problems existing in the above-mentioned prior art, the present application provides a method for preparing a lithium tantalate single crystal film, which can realize the preparation of a lithium tantalate single crystal film with controllable thickness over a large area. It mainly includes the following steps: growing a lithium tantalate single crystal on a lithium niobate wafer, bonding one side of the lithium tantalate to a carrier, first thinning the lithium niobate single crystal to less than 50μm by thinning, and then using the difference in corrosion rate between the lithium niobate single crystal and the lithium tantalate single crystal, using hydrofluoric acid, aqua regia and other acid solutions to etch away the upper lithium niobate single crystal, and finally obtaining a nanoscale large-size high-quality lithium tantalate single crystal film bonded to the carrier. This method has the advantages of low cost, high crystal quality, and controllable thickness, and can realize the preparation of nanoscale lithium tantalate single crystal films.
[0040] In one embodiment, a method for preparing a lithium tantalate single crystal thin film comprises the following steps:
[0041] S1. Provide a carrier wafer and a lithium niobate single crystal substrate;
[0042] S2, epitaxially growing a lithium tantalate single crystal layer on the lithium niobate single crystal substrate;
[0043] S3, bonding one side of the lithium tantalate single crystal layer of the lithium niobate single crystal substrate to the carrier wafer by means of a curing adhesive to obtain a bonding wafer;
[0044] S4, thinning the lithium niobate single crystal substrate in the bonding sheet to form a lithium niobate single crystal thin film;
[0045] S5. Chemically corrode the lithium niobate single crystal film until the lithium tantalate single crystal layer is exposed, thereby obtaining the lithium tantalate single crystal film bonded to the carrier.
[0046] In the present application, lithium niobate single crystal has the same structure as lithium tantalate single crystal and has similar lattice parameters, and large-sized lithium niobate wafers are easier to produce. Therefore, lithium niobate single crystal is selected as the substrate to facilitate the growth of large-sized epitaxial lithium tantalate single crystal films.
[0047] In one embodiment, in step S2, the thickness of the lithium tantalate single crystal layer is less than or equal to 20 μm.
[0048] The method for epitaxially growing a lithium tantalate single crystal layer on the lithium niobate single crystal substrate described in the present application is not strictly limited. A person skilled in the art can select from the existing technology as needed, for example, it can be selected from electron beam evaporation, thermal evaporation, high temperature sublimation, magnetron sputtering and other processes to epitaxially grow a lithium tantalate single crystal film, and a lithium tantalate single crystal film with a thickness of less than 20 μm can be prepared by adjusting the process. Among them, for evaporation methods such as electron beam evaporation and thermal evaporation, high-purity lithium tantalate ceramics can be used as raw materials, and by controlling the evaporation conditions, selecting appropriate power, evaporation rate, vacuum degree, substrate temperature, etc., it is possible to transform from the source material to a gas state and deposit in a relatively stable state while ensuring that the chemical bonds of the lithium tantalate are not destroyed; for magnetron sputtering, high-purity lithium tantalate ceramics or lithium tantalate single crystals can be used as target materials, and by selecting appropriate sputtering power, sputtering partial pressure, substrate temperature, etc., a suitable sputtering rate is controlled to achieve the preparation of a nano-scale lithium tantalate single crystal film with controllable thickness.
[0049] In one embodiment, in step S1, the carrier is selected from one of glass, silicon wafer, and flexible polymer film.
[0050] In one embodiment, in step S3, the curing adhesive is selected from one of an indegradable curing adhesive, a degradable light-curing adhesive, and a degradable heat-curing adhesive.
[0051] The method for bonding one side of the lithium tantalate single crystal layer of the lithium niobate single crystal substrate to the carrier through a curing adhesive described in the present application is not strictly limited. For example, the curing adhesive can be spin-coated on the carrier, and the one side of the lithium tantalate single crystal layer of the lithium niobate single crystal substrate can be bonded to the carrier using a bonding machine.
[0052] In one embodiment, in step S4, the thickness of the lithium niobate single crystal film is less than or equal to 50 μm.
[0053] In one embodiment, in step S4, the thinning of the lithium niobate single crystal substrate in the bonding wafer is to thin the lithium niobate single crystal by mechanical thinning, and the lithium niobate single crystal is ground and thinned to less than 50 μm.
[0054] In one embodiment, in step S5, the chemical etching step includes immersing the bonding wafer after forming the lithium niobate single crystal thin film in an etching solution;
[0055] The etching solution is selected from at least one of hydrofluoric acid, concentrated sulfuric acid, aqua regia, and BOE solution.
[0056] In the chemical etching process of the present application, the niobium (Nb) element in lithium niobate (LiNbO3) reacts easily with hydrofluoric acid to generate the corresponding niobium fluoride complex and be corroded. The lithium tantalate single crystal has high hardness and stability and exhibits a slower corrosion rate during the corrosion process. Therefore, the present application utilizes that the corrosion rate of the lithium niobate single crystal is much greater than that of the lithium tantalate single crystal. By controlling the composition of the etching solution and the etching time, the difference in corrosion rate can be used to achieve "self-stop corrosion", thereby obtaining a lithium tantalate single crystal film.
[0057] In one embodiment, in step S5, after obtaining the lithium tantalate single crystal film bonded to the carrier wafer, the step further includes washing the surface of the lithium tantalate single crystal film to remove residual corrosive solution.
[0058] In one embodiment, in step S5, after the chemical etching is performed to expose the lithium tantalate single crystal layer, the step further includes performing surface treatment on the lithium tantalate single crystal layer.
[0059] In the present application, the purpose of the surface treatment is to eliminate the uneven structure or impurities that may exist on the surface of the lithium tantalate single crystal layer after the etching solution treatment.
[0060] In one embodiment, the surface treatment method is not strictly limited, and can be, for example, selected from surface annealing and polishing.
[0061] In one embodiment, the steps further include:
[0062] The lithium tantalate single crystal film bonded to the carrier is debonded to obtain the separated lithium tantalate single crystal film.
[0063] In one embodiment, the size of the lithium tantalate single crystal film is 4 to 12 inches.
[0064] The method for preparing lithium tantalate single crystal thin film can be used in the application of preparing devices. After preparing the lithium tantalate film, the lithium tantalate single crystal thin film device can be prepared and processed first. After bonding, the lithium niobate single crystal can be removed by back thinning and chemical etching in sequence. The specific operation scheme is as follows: After the lithium tantalate single crystal thin film is prepared, the lithium tantalate single crystal thin film device array is prepared according to the device structure designed in advance, combined with semiconductor processes such as lithography and etching. The lithium tantalate face is temporarily bonded to the glass carrier using a debondable adhesive, and then the lithium niobate single crystal is removed by thinning and etching. After processing, the lithium tantalate single crystal thin film can be separated from the temporary carrier by a debonding process, and transferred to other carriers for bonding.
[0065] In one embodiment, the lithium tantalate single crystal thin film preparation method is used in the preparation of electronic devices and optical devices, and the lithium tantalate single crystal thin film preparation method further includes the following steps:
[0066] After epitaxially growing a lithium tantalate single crystal layer on the lithium niobate single crystal substrate, a device array is prepared on the lithium tantalate single crystal layer by a semiconductor process;
[0067] After obtaining the lithium tantalate single crystal film bonded to the carrier, the side of the lithium tantalate single crystal film facing away from the carrier is bonded to a target substrate, and then the carrier and the lithium tantalate single crystal film are separated by debonding.
[0068] To more clearly describe the technical solution of the present application, in one embodiment, in combination with the attached Figure 1-5 This application describes in further detail:
[0069] like Figure 1 As shown, the method for preparing a lithium tantalate single crystal thin film includes the following steps:
[0070] Step S1: Preparation of lithium tantalate single crystal film. Lithium niobate single crystal has the same structure as lithium tantalate single crystal and has similar lattice parameters, and large-sized lithium niobate wafers are easier to obtain. Therefore, lithium niobate single crystal is selected as the substrate to facilitate the growth of large-sized epitaxial lithium tantalate single crystal film. On the lithium niobate single crystal substrate, the lithium tantalate single crystal film is epitaxially grown by electron beam evaporation, thermal evaporation, high temperature sublimation, magnetron sputtering and other processes. The lithium tantalate single crystal film with a thickness of less than 20μm can be prepared by adjusting the process. For evaporation methods such as electron beam evaporation and thermal evaporation, high-purity lithium tantalate ceramics can be used as raw materials. By controlling the evaporation conditions and selecting appropriate power, evaporation rate, vacuum degree, substrate temperature (650°C to 1200°C), the source material can be transformed into a gaseous state and deposited in a relatively stable state while ensuring that the chemical bonds of lithium tantalate are not destroyed. For magnetron sputtering, high-purity lithium tantalate ceramics or lithium tantalate single crystals can be used as target materials. By selecting appropriate sputtering power, sputtering partial pressure, substrate temperature, etc., and controlling the appropriate sputtering rate, a nanoscale lithium tantalate single crystal film with controllable thickness can be prepared. The cross-sectional view of the prepared lithium tantalate single crystal film is shown below. Figure 2 shown.
[0071] Step S2: Bonding. Spin-coat the curing glue on the carrier, and use a bonding machine to bond the lithium tantalate surface to the carrier. The carrier used includes but is not limited to glass, silicon wafer, flexible polymer film, etc.; the curing glue used in bonding includes but is not limited to non-solvable curing glue, resolvable light-curing glue, resolvable heat-curing glue, etc. The cross-sectional view of the prepared lithium tantalate single crystal film after bonding with the carrier is as follows: Figure 3 shown.
[0072] Step S3: Thinning the lithium niobate single crystal. The lithium niobate single crystal is thinned by mechanical thinning, and the lithium niobate single crystal is ground and thinned to less than 50 μm to obtain a cross-sectional view of the thinned lithium niobate single crystal as shown in FIG. Figure 4 shown.
[0073] Step S4: chemically corroding lithium niobate. The niobium (Nb) element in lithium niobate (LiNbO3) is more likely to react with hydrofluoric acid to generate the corresponding niobium fluoride complex and be corroded. Tantalum (Ta) in lithium tantalate (LiTaO3) is relatively resistant to hydrofluoric acid corrosion. This is because although tantalum and niobium belong to the same group of elements, tantalum has higher chemical stability in such an acidic environment. Therefore, lithium tantalate single crystals have higher hardness and stability, and show a slower corrosion rate during the corrosion process. In contrast, lithium niobate single crystals have a slightly lower hardness, and under the action of specific corrosive agents, their corrosion rate can be relatively fast. Since the corrosion rate of lithium niobate single crystals is much greater than that of lithium tantalate single crystals, the difference in corrosion rate can be used to achieve "self-stop corrosion" by controlling the composition of the etching solution and the etching time, thereby obtaining a lithium tantalate single crystal film. The etching solution includes but is not limited to hydrofluoric acid (HF), a mixture of HF and concentrated sulfuric acid (H2SO4) in a specific ratio, aqua regia (a mixture of concentrated hydrochloric acid and concentrated nitric acid in a specific ratio), etc. After the corrosion, the residual corrosion liquid on the surface of the lithium tantalate single crystal film was cleaned with deionized water to prepare the cross-sectional view of the lithium tantalate single crystal film. Figure 5 As shown;
[0074] Step S5: Surface treatment of lithium tantalate single crystal film. The single crystal surface after acid treatment may have uneven structure or impurities, so the lithium tantalate film needs to be treated by surface annealing, polishing, etc. to remove surface impurities and reduce surface roughness.
[0075] In the embodiment of the present application, the bonding strength, bonding time, wavelength of the light source selected for curing, energy level and time are all determined by the composition of the curing adhesive, and the composition of the light-curing adhesive can be adjusted according to different requirements.
[0076] Example 1
[0077] Step S1: Preparation of lithium tantalate single crystal thin film
[0078] An 8-inch lithium niobate single crystal was selected as the substrate and a high-purity lithium tantalate ceramic was used as the target. The lithium tantalate single crystal film was prepared by magnetron sputtering. The specific steps were as follows: the vacuum chamber was pumped down to 10 -4Pa, set the substrate temperature to 650℃, turn on the gas control device, introduce oxygen and argon (in a ratio of 1:4) into the vacuum chamber, so that the vacuum chamber pressure is about 0.5Pa, turn on the RF power supply, adjust the RF power to 150W, pre-sputter for one minute to remove impurities on the target surface, open the baffle, and start formal sputtering. After sputtering for 0.5h, a lithium tantalate single crystal film with a thickness of about 50nm is obtained on the surface of the lithium niobate single crystal.
[0079] Step S2: Bonding
[0080] Select an 8-inch glass sheet as a carrier, place it on the vacuum adsorption tray in the glue spreader, evenly drop an appropriate amount of non-degradable bonded photocurable glue on the surface, set the rotation speed to 6000rpm / min, spin coat for 1 minute, and then use a bonding machine to align one side of the lithium tantalate single crystal film of the substrate with the glue-coated surface of the glue-coated glass sheet and bond them under pressure. Take out the sample and transfer it to the photocuring equipment. Use ultraviolet light to irradiate the sample for 1 minute to cure the glue to obtain a bonded sheet.
[0081] Step S3: Thinning of lithium niobate single crystal
[0082] The bonding wafer is placed in the tray of the thinning machine, and a 1000-mesh grinding wheel is used to quickly thin the thickness of the lithium niobate single crystal on the bonding wafer to 50 microns through rough thinning.
[0083] Step S4: Chemical etching of lithium niobate
[0084] A mixed solution of hydrofluoric acid (HF): ammonium fluoride (NH4F): water (H2O) is prepared as an etching solution (including 30 mL of hydrofluoric acid (48%), 60 g of ammonium fluoride, and 100 mL of deionized water). The thinned bonding wafer is immersed in a closed container filled with the etching solution, and the difference in corrosion rate is used to achieve "self-stop corrosion". The lithium niobate single crystal on the bonding wafer is corroded to obtain a lithium tantalate single crystal film. After corrosion, the residual etching solution on the surface of the lithium tantalate single crystal film is cleaned with deionized water.
[0085] Step S5: Surface treatment of lithium tantalate single crystal film
[0086] The corroded lithium tantalate single crystal film is single-sided polished using a single polishing machine and polishing liquid. Nano-silicon dioxide polishing liquid is used and the polishing pressure is controlled between 0.01MPa to achieve lower roughness and higher flatness.
[0087] Example 2
[0088] Step S1: Preparation of lithium tantalate single crystal thin film
[0089] An 8-inch lithium niobate single crystal was selected as the substrate, and high-purity lithium tantalate ceramics were used as the raw material. The lithium tantalate single crystal film was prepared by electron beam evaporation. The specific steps were as follows: the vacuum chamber was evacuated to 10-4 Pa, then the heater temperature was raised to 650°C, and oxygen was introduced until the chamber pressure reached 10 -2 Pa, turn on the electron gun power supply to make the electron beam bombard the surface of the lithium tantalate ceramic in the crucible. After the gas pressure, beam current and evaporation rate are stable, remove the sample baffle and deposit the lithium tantalate film. A lithium tantalate single crystal film with a thickness of about 500nm is deposited on the surface of the lithium niobate single crystal.
[0090] Steps S2 to S5 are the same as the corresponding steps S1 to S5 of the first embodiment.
[0091] Example 3
[0092] Step S1: Preparation of lithium tantalate single crystal thin film
[0093] An 8-inch lithium niobate single crystal was selected as the substrate and a high-purity lithium tantalate ceramic was used as the target. The lithium tantalate single crystal film was prepared by magnetron sputtering. The specific steps were as follows: the vacuum chamber was pumped down to 10 -4 Pa, set the substrate temperature to 650℃, turn on the gas control device, introduce oxygen and argon (in a ratio of 1:4) into the vacuum chamber, so that the vacuum chamber pressure is about 0.5Pa, turn on the RF power supply, adjust the RF power to 150W, pre-sputter for one minute to remove impurities on the target surface, open the baffle, and start formal sputtering. After sputtering for 0.5h, a lithium tantalate single crystal film with a thickness of about 50nm is obtained on the surface of the lithium niobate single crystal.
[0094] Step S2: Device structure processing
[0095] According to the required device structure, the lithium tantalate single crystal film is processed by semiconductor processes such as photolithography and etching in sequence to form a device array on the lithium tantalate single crystal film.
[0096] Step S3: Bonding
[0097] Select an 8-inch glass sheet as a carrier, place it on the vacuum adsorption tray in the glue spreader, evenly drop an appropriate amount of laser debonding photocuring glue on the surface, set the rotation speed to 6000rpm / min, spin coat for 1min, and then use a bonding machine to align one side of the lithium tantalate single crystal film of the substrate with the glue-coated surface of the glue-coated glass sheet and bond them under pressure. Take out the sample and transfer it to the photocuring equipment. Use ultraviolet light to irradiate the sample for 1min to cure the glue to obtain a bonded sheet.
[0098] Step S4: Thinning of lithium niobate single crystal
[0099] The bonding wafer is placed in the tray of the thinning machine, and a 1000-mesh grinding wheel is used to quickly thin the thickness of the lithium niobate single crystal on the bonding wafer to 50 microns through rough thinning.
[0100] Step S5: Chemical etching of lithium niobate
[0101] A mixed solution of hydrofluoric acid (HF): ammonium fluoride (NH4F): water (H2O) is prepared as an etching solution (including 30 mL of hydrofluoric acid (48%), 60 g of ammonium fluoride, and 100 mL of deionized water). The thinned bonding wafer is immersed in a closed container filled with the etching solution, and the difference in corrosion rate is used to achieve "self-stop corrosion". The lithium niobate single crystal on the bonding wafer is corroded to obtain a lithium tantalate single crystal film. After corrosion, the residual etching solution on the surface of the lithium tantalate single crystal film is cleaned with deionized water.
[0102] Step S6: Surface treatment of lithium tantalate single crystal film
[0103] The corroded lithium tantalate single crystal film is single-sided polished using a single polishing machine and polishing liquid. Nano-silicon dioxide polishing liquid is used and the polishing pressure is controlled between 0.01MPa to achieve lower roughness and higher flatness.
[0104] Step S7: Lithium tantalate single crystal thin film transfer
[0105] The lithium tantalate single crystal film surface is bonded to the Si wafer using a non-debonding photocuring adhesive, and then the lithium tantalate single crystal film is separated from the glass carrier using a laser debonding method.
[0106] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a lithium tantalate single crystal thin film, characterized in that: The steps include: Provide carrier wafers and lithium niobate single crystal substrates; epitaxially growing a lithium tantalate single crystal layer on the lithium niobate single crystal substrate; Bonding one side of the lithium tantalate single crystal layer of the lithium niobate single crystal substrate to the carrier through a curing adhesive to obtain a bonding sheet; Thinning the lithium niobate single crystal substrate in the bonding sheet to form a lithium niobate single crystal film; The lithium niobate single crystal film is chemically etched until the lithium tantalate single crystal layer is exposed, thereby obtaining the lithium tantalate single crystal film bonded to the carrier.
2. The method for preparing a lithium tantalate single crystal thin film according to claim 1, characterized in that: The thickness of the lithium tantalate single crystal layer is less than or equal to 20 μm.
3. The method for preparing a lithium tantalate single crystal thin film according to claim 1, characterized in that: The thickness of the lithium niobate single crystal film is less than or equal to 50 μm.
4. The method for preparing a lithium tantalate single crystal thin film according to claim 1, characterized in that: The chemical etching step includes immersing the bonding sheet after forming the lithium niobate single crystal thin film in an etching solution; The etching solution is selected from at least one of hydrofluoric acid, concentrated sulfuric acid, aqua regia, and BOE solution.
5. The method for preparing a lithium tantalate single crystal thin film according to claim 1, characterized in that: After the chemical etching is performed to expose the lithium tantalate single crystal layer, the method further includes performing surface treatment on the lithium tantalate single crystal layer.
6. The method for preparing a lithium tantalate single crystal thin film according to claim 1, characterized in that: The steps also include: The lithium tantalate single crystal film bonded to the carrier is debonded to obtain the separated lithium tantalate single crystal film.
7. The method for preparing a lithium tantalate single crystal thin film according to claim 1, characterized in that: The carrier is selected from glass, silicon wafer, and flexible polymer film.
8. The method for preparing a lithium tantalate single crystal thin film according to claim 1, characterized in that: The size of the lithium tantalate single crystal film is 4 to 12 inches.
9. Application of the method for preparing a lithium tantalate single crystal thin film according to any one of claims 1 to 8 in preparing electronic devices and optical devices.
10. The use according to claim 9, characterized in that: The method for preparing the lithium tantalate single crystal thin film also includes the following steps: After epitaxially growing a lithium tantalate single crystal layer on the lithium niobate single crystal substrate, a device array is prepared on the lithium tantalate single crystal layer by a semiconductor process; After obtaining the lithium tantalate single crystal film bonded to the carrier, the side of the lithium tantalate single crystal film facing away from the carrier is bonded to a target substrate, and then the carrier and the lithium tantalate single crystal film are separated by debonding.